2015
DOI: 10.1089/bfm.2014.0128
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Breastfeeding on Serum Asymmetric Dimethylarginine Levels and Body Composition in Children

Abstract: Introduction: The purpose of this work was to investigate the association of serum asymmetric dimethylarginine (ADMA) and high-sensitivity C-reactive protein (hs-CRP) levels with duration of breastfeeding and body composition in children. Patients and Methods: The study group consisted of 88 patients with a median age of 12 months (42 boys, 46 girls), classified as never breastfed or fully breastfed. ADMA and hs-CRP were measured by immunoenzymatic enzyme-linked immunosorbent assay commercial kits. Body compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In contrast, there was a strong relation between duration of breast-feeding for three or more months and lower CRP levels in women. Although there some studies have reported that no significant increases in serum CRP between breastfed participants and those never breastfed [38]. There are several possible explanations, where breastfeeding might influence low-grade inflammation only in people who are predisposed to genetic problem.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, there was a strong relation between duration of breast-feeding for three or more months and lower CRP levels in women. Although there some studies have reported that no significant increases in serum CRP between breastfed participants and those never breastfed [38]. There are several possible explanations, where breastfeeding might influence low-grade inflammation only in people who are predisposed to genetic problem.…”
Section: Discussionmentioning
confidence: 97%
“…Scarce data from the literature indicate that ADMA is increased in obesity or the metabolic syndrome [24]. In healthy young adults ADMA showed a positive association with body weight, BMI, WC, WHtR and body FM studied by BIA [25]. A positive correlation was found between ADMA and body mass in healthy 1-year old children [19].…”
Section: Association Of Obesity Indices Body Composition and Biochemmentioning
confidence: 97%
“…Optimal nutrition during childhood is critical to support the growth and development during the first 12 months following birth. 16 The current study evaluated rat deprived of breast milk at 14 days, when it begins the consumption of solid food. At this age, pups still breastfeed, but they can survive independently of their mothers.…”
Section: Discussionmentioning
confidence: 99%